NiFe Alloy Nanoparticles with hcp Crystal Structure Stimulate Superior Oxygen Evolution Reaction Electrocatalytic Activity. Issue 18 (26th March 2019) - Wang, Changhong; Yang, Hongchao; Zhang, Yejun; Wang, Qiangbin
Abstract: Tuning the crystal phase of metal alloy nanomaterials has been proved a significant way to alter their catalytic properties based on crystal structure and electronic property. Herein, we successfully developed a simple strategy to controllably synthesize a rare crystal structure of hexagonal close‐packed (hcp) NiFe nanoparticle (NP) encapsulated in a N‐doped carbon (NC) shell (hcp‐NiFe@NC). Then, we systemically investigated the oxygen evolution reaction (OER) performance of the samples under alkaline conditions, in which the hcp‐NiFe@NC exhibits superior OER activity compared to the conventional face‐centered cubic (fcc) NiFe encapsulated in a N‐doped carbon shell (fcc‐NiFe@NC). At the current densities of 10 and 100 mA cm −2, the hcp‐NiFe@NC with Fe/Ni ratio of ≈5.4 % only needs ultralow overpotentials of 226 mV and 263 mV versus reversible hydrogen electrode in 1.0 m KOH electrolyte, respectively, which were extremely lower than those of fcc‐NiFe@NC and most of other reported NiFe‐based electrocatalysts. We proposed that hcp‐NiFe possesses favorable electronic property to expedite the reaction on the NC surface, resulting higher catalytic activity for OER. This research provides a new insight to design more efficient electrocatalysts by considering the crystal phase correlated electronic property. Abstract : Hcp‐NiFe alloy nanoparticles encapsulated in N‐doped carbon shells (hcp‐NiFe@NC) were successfully synthesized through a facile MOF‐annealing strategy. Benefiting from the crystal structure and electronic property, the hcp‐NiFe@NC exhibits outstanding OER performance over the conventional fcc‐NiFe@NC catalyst.